2009
DOI: 10.1007/s11145-009-9182-x
|View full text |Cite
|
Sign up to set email alerts
|

Reading electronic and printed books with and without adult instruction: effects on emergent reading

Abstract: The effects of electronic book (e-book) and printed book reading on children's emergent reading with and without adult instruction were investigated. One hundred twenty-eight 5-to 6-year-old kindergarten children from low SES families were randomly assigned to one of four groups (32 children each):(1) independently reading the e-book (EB); (2) reading the e-book with adult instruction (EBI); (3) reading the printed book with adult instruction (PBI); and (4) receiving the regular kindergarten program (control).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 61 publications
2
56
1
2
Order By: Relevance
“…Korat and Shamir (2007) reported similar vocabulary development in the two media. The advantage of the E-book format regarding knowledge about print is noticed only when the E-book format has been pitched against a regular kindergarten program or when the E-book and the printed book were compared to a regular kindergarten program (Korat & Shamir, 2004;Segal-Drori et al, 2009). In this study, following intervention, the print condition benefitted more plot understanding, knowledge about print, and vocabulary scores compared with the electronic condition.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Korat and Shamir (2007) reported similar vocabulary development in the two media. The advantage of the E-book format regarding knowledge about print is noticed only when the E-book format has been pitched against a regular kindergarten program or when the E-book and the printed book were compared to a regular kindergarten program (Korat & Shamir, 2004;Segal-Drori et al, 2009). In this study, following intervention, the print condition benefitted more plot understanding, knowledge about print, and vocabulary scores compared with the electronic condition.…”
Section: Discussionmentioning
confidence: 57%
“…The studies revealed an advantage to the E-book over the printed book on phonological awareness (Korat & Shamir , 2004;Segal-Drori, Korat, Shamir, & Klein, 2009), vocabulary (Korat & Shamir, 2004;Segal-Drori et al, 2009), and knowledge about print (Korat & Shamir, 2004;Segal-Drori et al, 2009 ). In these studies there is slight advantage for reading an E-book with an adult over reading a printed book with mediation (Korat & Shamir, 2004Segal-Drori et al, 2009).…”
Section: Studies Comparing E-book Printed Book Reading and The Regumentioning
confidence: 91%
See 1 more Smart Citation
“…Scientific evaluations of these technologies have found that, although engaging, such devices do not effectively achieve educational goals when used alone (Korat and Shamir 2008). Instead, recent studies highlight the importance of joint parent-child reading, show- ing that learning gains are achieved by combining the use of digital media with adult interaction (Segal-Drori et al 2010). Interactive stories tend to distract readers with multimedia features without increasing the dialog between parents and children during reading, which results in lower learning rates (Parish-Morris et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, as they introduce communications technology in their teaching, in their internship practice, and in their first year as novice teachers, studentteachers already encounter many difficulties such as: a gap between theory and the reality in the field that influences and creates different pressures such as: time pressure, disciplinary problems etc. (Segal-Drori et al, 2009). Therefore, the relevant knowledge that needs to be taken into account when training teachers is content-pedagogic-technological knowledge (Mishra & Koehler, 2006).…”
Section: Introductionmentioning
confidence: 99%